2007
DOI: 10.1021/jp068902v
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Shrinkage and Re-expansion of a Single Aqueous Droplet inside an Optical Vortex Trap

Abstract: This paper describes the shrinkage and re-expansion of individual femtoliter-volume aqueous droplets that were suspended in an organic medium and held in an optical vortex trap. To elucidate the mechanism behind this phenomenon, we constructed a heat and mass transfer model and carried out experimental verifications of our model. From these studies, we conclude that an evaporation mechanism sufficiently describes the shrinkage of aqueous droplets held in a vortex trap, while a mechanism based on the supersatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…It was also found that the droplets remained intact for over 24 hours provided that no droplet shrinkage was observed. Interestingly it was noted that this shrinkage phenomenon, which has been reported previously for similarly sized microdroplets in oil, [22][23][24][25][26] was not routinely observed in our experiments. We speculate that this may be due to the inevitable variability of the water to oil ratio of the final microdroplet dispersion manually dispensed into the well.…”
supporting
confidence: 66%
“…It was also found that the droplets remained intact for over 24 hours provided that no droplet shrinkage was observed. Interestingly it was noted that this shrinkage phenomenon, which has been reported previously for similarly sized microdroplets in oil, [22][23][24][25][26] was not routinely observed in our experiments. We speculate that this may be due to the inevitable variability of the water to oil ratio of the final microdroplet dispersion manually dispensed into the well.…”
supporting
confidence: 66%
“…One remarkable characteristic of vortex trapping of aqueous droplets, we found, is the ability to tune dynamically the concentration of contained molecules 21,36,37 Figure 8. shows our experimental findings, in which the optical vortex trap slowly “peeled off” layers of water molecules at the interface of the aqueous and immiscible fluids, thus concentrating the encapsulated molecules that were retained within the droplet.…”
Section: Droplet Manipulationsmentioning
confidence: 82%
“…Once formed, droplets can be manipulated with a wide range of physical mechanisms, such as pressure, dielectrophoresis, 47 magnetic fields, 48 optical fields, 29,49 and thermal gradients. 50,51 Some methods can be used to manipulate a fast-flowing stream of droplets in a high-throughput format, whereas others are best suited for controlling individual droplets.…”
Section: Droplet Manipulationmentioning
confidence: 99%
“…12,14,49 In Figure 3d, a droplet is held by an optical vortex trap, 12,13,49,53 shrinks in volume, and upon release from the trap or when the power of the trap is lowered, becomes larger again. An optical vortex trap is formed using a class of laser beam called the Laguerre–Gaussian beam, which is characterized by a helical phase distribution across its wave front that results in the formation of a stably propagating dark core.…”
Section: Droplet Manipulationmentioning
confidence: 99%